PRILOG POZNAVANJU DIPLOMATIČKIH ZNAČAJKI ISPRAVE KOJOM JE KRALJ LUDOVIK I. ANŽUVINAC KOPRIVNICI 4. STUDENOGA 1356. PODIJELIO POVLASTICE SLOBODNOG I KRALJEVSKOG GRADA - Petrić, Hrvoje (Array, 2005)
Based on the current knowledge in historiography and available sources, the author provides a contribution to studies of diplomatic importance and characteristics of a royal charter, the king Ludovicus I. Anjou granted the town of Koprivnica the privileges of a free, royal borough. In his introduction, the author speaks of the charter itself which the king Ludovicus I. Anjou issued, and basic information on the origins of the medieval civic settlement of Koprivnica, with a summary of other, former privileges – granted in 1338 and 1353. It’ s followed by analysis of the Croatian translation of this charter issued by the Croato-Hungarian king Ludovicus I. Anjou on 4 November 1356. The author also analyzes internal and external characteristics of the charter, as well as establishing its authenticity.